2020
DOI: 10.1111/sjos.12475
|View full text |Cite
|
Sign up to set email alerts
|

Linear censored quantile regression: A novel minimum‐distance approach

Abstract: In this article, we investigate a new procedure for the estimation of a linear quantile regression with possibly right-censored responses. Contrary to the main literature on the subject, we propose in this context to circumvent the formulation of conditional quantiles through the so-called "check" loss function that stems from the influential work of Koenker and Bassett (1978). Instead, our suggestion is here to estimate the quantile coefficients by minimizing an alternative measure of distance. In fact, our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…De backer et al in their study indicated in an extensive simulation study that the resulted quantile regression estimator respect to established check-based formulations have less variance results. From a theoretical prospect, both consistency and asymptotic normality of the proposed estimator for linear regression are obtained under classical regularity conditions 10 . Yang et al indicated that the Yang's method presents an estimator is able to achieve significant efficiency gains in comparisons with Portnoy’s estimator 9 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…De backer et al in their study indicated in an extensive simulation study that the resulted quantile regression estimator respect to established check-based formulations have less variance results. From a theoretical prospect, both consistency and asymptotic normality of the proposed estimator for linear regression are obtained under classical regularity conditions 10 . Yang et al indicated that the Yang's method presents an estimator is able to achieve significant efficiency gains in comparisons with Portnoy’s estimator 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The most applying methods during the recent years are Portnoy 5 , Wang and Wang 7 , Bottai and Zhang 8 , Yang et al 9 and De Backer et al 10 methods. In the following, we present a brief overview of methodological framework for these models.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations